The new emerging of diabetes treatment: a review of oral insulin / Jihan Maftuuhatus Zuhra [et al.] - Zuhra, Jihan Maftuuhatus; Emad, Rand Omar; Kamarudin, Nur Ain Nabihah; Zulkifli, Nur Wahida (Faculty of Pharmacy, 2023)
Diabetes patients typically get daily subcutaneous insulin injections; however, due to the discomfort of these injections, patient compliance is difficult to maintain; hence, several delivery methods, including oral administration, are being investigated. The emerging field of oral insulin administration is summarised in this overview. There are many formulations to develop oral insulin, such as PEGylation of insulin, targeting moieties-mediated transport strategy, cell penetrating peptides (cpps)-assisted permeation strategy, smart oral robotics-associated traverse strategy, hydrogels for insulin: microenvironment-responsive hydrogels, and zwitterionic micelles. Future oral insulin development will be resolved by non-erratic absorption and bioavailability. One method to deliver the therapeutic ingredient to the colon, improve insulin bioavailability, and eliminate small intestine absorption variation is to include compatible and appropriate excipients in an insulin tablet, such as an acid-resistant enteric coating, enzyme inhibitor, absorption enhancer, and mucoadhesive polymer.